The metamorphoses of the hero in Iakovos Kambanellis’ Ulysses, Come Home (Minerva, 2021)
In the play Ulysses, Come Home, whose first version dates from 1952 and whose first performance dates from 1966, the Greek playwright Iakovos Kambanellis offers a parodic and satirical re-reading of the Odyssey. This paper analyses some of the key elements of this re-reading, focusing on the topics that the author takes from Homer, especially in the characterization of the hero and in the use of the Homeric motif of metamorphosis and anagnorisis. The play is also placed in the context of the demythologisation and anti-heroic reception of Homer in the 20th century.
Keywords: Kambanellis; Homer; Odyssey; Classical Reception; Modern Greek Theatre